Smart transportation system for smart cities - Yeo, Brandon Wen Jun (2018)
Intelligent Transport Systems (ITS) are common tools to help monitor traffic trends which aids in traffic analysis. An increase in the number of vehicles on Singapore’s road, creates challenges in effective traffic management.